An apostolic gospel the "Epistula apostolorum" in literary context - Watson, Francis 1956- (New York University of Cambridge ESOL Examinations, 2020)
Built around a new translation of a neglected text, this book offers new perspectives on early gospel literature.
Cover -- Half-title -- Series information -- Title page -- Copyright information -- Contents -- Acknowledgements -- Introduction -- I -- II -- III -- Part I Recovering the Epistula -- 1 An Ambiguous Legacy: The Epistula Apostolorum and its Editors -- 1.1 The Coptic Text and its Discoverer(s) -- 1.2 The Latin Title -- 1.3 Two Ethiopic Testaments -- 1.4 The Problem of Co-ordination -- 2 Translation -- Confession of Faith -- The Miracle Cycle -- Recapitulation: Reasons for Writing -- The Dawn of Easter Faith -- The Descent through the Heavens -- Pascha and Parousia -- The Interim -- The Resurrection of the Flesh -- The Descent into Hell -- Other Teachings -- Mission -- Paul the Persecutor and Confessor -- The Time of Trial -- The Fate of the Elect -- Divine Justice -- Ministry -- Parable of the Virgins -- Discipline -- Ascension -- Part II Themes -- 3 The Miracle Sequence -- 3.1 The Question of Genre -- (i) Warnings against False Apostles as Reason for Writing -- (ii) Confession of Faith -- (iii) Narrative Section (Miracle Sequence/Easter Day) -- 3.2 Tradition and Redaction -- 4 Resurrection and Eschatologies -- 4.1 Rewriting GJohn 20 -- 4.1.1 The Personnel at the Tomb -- 4.1.2 Apostolic Unbelief -- 4.1.3 Jesus' Feet -- 4.2 Contexts of Resurrection -- 4.2.1 Resurrection of the Flesh -- 4.2.2 Individual and Cosmos -- 5 Narratives of Incarnation -- 5.1 Angelic Transformations (1): The Self-Incarnation of the Logos -- 5.2 Angelic Transformations (2): The Hiddenness of the Lord -- 5.3 Incarnation and Virgin Birth -- 5.4 The Descent of the Christ -- 6 Paul and the Apostolic Mission -- 6.1 Questioning Matthew -- 6.2 Paul the Jew -- 6.3 Paul the Persecutor -- 6.4 The Conversion of Paul -- 7 Vindicating Divine Justice -- 7.1 Judgement: Scope and Criterion -- 7.2 Justice or Mercy? -- Part III Additional Notes on Text and Translation.
Description based on publisher supplied metadata and other sources
Keywords: Apostles; Electronic books